Strategi Peningkatan Mutu Pembelajaran pada Sekolah Unggulan: Studi Multi Situs di MI Darul Muta'alimin Patianrowo Nganjuk, MI Muhammadiyah 1 Pare dan SD Katolik Frateran 1 Kota Kediri - Solikah, Alfiatu (Didaktika Religia, 2014)
This paper deals with the available resources and strategies used to improve thequality of learning at excellent schools. The study was conducted at MI DarulMuta'alimin Patianrowo Nganjuk, MI Muhammadiyah 1 Pare and Catholicelementary Frateran 1 Kediri. Concurrent parallel design was used. It was foundout that excellent schools are not identical with expensive schools. Excellentschools improve their instructional quality through the organization of learningstrategies, delivery of instructional materials, and learning management strategy.